2005
DOI: 10.1021/jp053849g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Aspects of Hydrogen-Bonded Complexes and Inclusion Compounds Containing α,ω-Dicyanoalkanes and Urea, Investigated by Solid-State 13C and 2H NMR Techniques

Abstract: Solid-state 13C NMR and 2H NMR techniques have been used to investigate structural and dynamic properties of the 1,4-dicyanobutane/urea and 1,5-dicyanopentane/urea 1:1 hydrogen-bonded complexes and the 1,6-dicyanohexane/urea inclusion compound. The pure crystalline phase of urea has also been investigated. The 13C NMR studies have focused on 13C chemical shift anisotropy and second-order quadrupolar effects (arising from 13C-14N interaction) for the urea molecules and the cyano groups of the alpha,omega-dicyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…For rigid organic solids, a dipolar dephasing delay of 40 μs is generally sufficient to suppress the 13 C NMR signal for a 13 C nucleus directly bonded to 1 H, but when a 13 C− 1 H bond undergoes reorientational dynamics (as often observed in the case of methyl groups), a dipolar dephasing delay significantly longer than 40 μs is typically required to suppress the 13 C NMR signal. As can be see from Figure , the methyl groups in Trip(Et)−PIM and Trip( i -Pr)−PIM undergo significant reorientational dynamics, whereas the 13 C− 1 H bonds in the methylene group of Trip(Et)−PIM and in the methine group of Trip( i -Pr)−PIM do not undergo significant reorientation . For Trip(Me)−PIM, our results suggest that the methyl group undergoes reorientation, but that the reorientation is significantly more hindered than is typical for methyl groups in organic solids.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For rigid organic solids, a dipolar dephasing delay of 40 μs is generally sufficient to suppress the 13 C NMR signal for a 13 C nucleus directly bonded to 1 H, but when a 13 C− 1 H bond undergoes reorientational dynamics (as often observed in the case of methyl groups), a dipolar dephasing delay significantly longer than 40 μs is typically required to suppress the 13 C NMR signal. As can be see from Figure , the methyl groups in Trip(Et)−PIM and Trip( i -Pr)−PIM undergo significant reorientational dynamics, whereas the 13 C− 1 H bonds in the methylene group of Trip(Et)−PIM and in the methine group of Trip( i -Pr)−PIM do not undergo significant reorientation . For Trip(Me)−PIM, our results suggest that the methyl group undergoes reorientation, but that the reorientation is significantly more hindered than is typical for methyl groups in organic solids.…”
Section: Discussionmentioning
confidence: 54%
“…As can be see from Figure 1, the methyl groups in Trip(Et)-PIM and Trip(i-Pr)-PIM undergo significant reorientational dynamics, whereas the 13 C-1 H bonds in the methylene group of Trip(Et)-PIM and in the methine group of Trip(i-Pr)-PIM do not undergo significant reorientation. 124 For Trip(Me)-PIM, our results suggest that the methyl group undergoes reorientation, but that the reorientation is significantly more hindered than is typical for methyl groups in organic solids. Solution state NMR studies on triptycenes substituted with an isopropyl group at the bridgehead show that the activation energy for rotation about the C-CH(CH 3 ) 2 bond is in excess of 75 kJ mol -1 .…”
Section: Discussionmentioning
confidence: 67%
“…An iterative deconvolution of the spectrum using mixed Lorentzian (40 %) -Gaussian (60 %) lineshapes (Figure 3b, c) suggests that the use of three peaks at 163.9, 156.0, and 151.0 ppm is sufficient to reproduce the observed asymmetry in the low-frequency region (Figure 3c). The observed asymmetry of the low-frequency peak could be due to structural inhomogeneity as well as the effect of 13 C, 14 N residual dipolar couplings, that are known to be significant at a relatively low magnetic field of 7.05 T. [40] In the single-pulse MAS experiment, which is better suited for quantitative estimates than CP-MAS, the shoulder at δ = 151 ppm is significantly smaller ( Figure S3a In their study of TGCN, Algara-Siller et al observed a broad resonance spanning a similar range (145-172 ppm with a maximum near 160 ppm) to that observed for the Pharaoh's serpent material [13] ( Figure S4, Supporting Information). Although their sample was nominally H-free, both 1 Figure S5, Supporting Information), [36] similar to those observed for the Pharaoh's serpent.…”
Section: Articlementioning
confidence: 99%
“…45,46 The analysis of the motional averaging effects on individual CSA components is often used to deduce the geometry of the motion. 13,[47][48][49] The procedure used to calculate the components of the motionally averaged CSA in the rapid motion regime and to determine the angular parameters that characterize the geometry of motion has been described previously. 13 …”
Section: Chemical Shift Anisotropymentioning
confidence: 99%